Predictive significance of 18F-FDG PET/CT metabolic parameters for the expression level of HER2 in gastric cancer - Shilai, Zhang; Shaozhou, Mo; Linlin, Wei; Hua, Chai; Weiwei, Pu; Ziya, Liu; Wenming, Qiu; Zhi, Yang; Hai, Liao; Guoyou, Xiao (Frontiers in Oncology, 2025)
ObjectiveTo investigate the predictive value of pertinent metabolic parameters of 18F-FDG PET/CT in relation to the expression level of human epidermal growth factor receptor 2 (HER2) in patients with gastric cancer.Materials and methodsThe data was retrospectively acquired from 105 patients who had been pathologically diagnosed gastric cancer prior to treatment at our institution, including clinical data, laboratory test results, histological information, 18F-FDG PET/CT metabolic parameters (including maximum standardized uptake value (SUVmax), mean standardized uptake value (SUVmean), peak standardized uptake value (SUVpeak), SUVmax normalized by lean body mass (SULmax), SUVmean normalized by lean body mass (SULmean), SUVpeak normalized by lean body mass (SULpeak), metabolic tumor volume (MTV), and total lesion glycolysis (TLG)), and HER2 expression level, from January 2018 to December 2022. The correlation between 18F-FDG PET/CT metabolic parameters and HER2 expression level was examined, and the predictive value of these measures for HER2 expression level was investigated.ResultsAmong the 105 patients, 27 exhibited positive HER2 expression, while 78 demonstrated negative HER2 expression. Significant differences in MTV and TLG between patients exhibiting positive and negative HER2 expression (P < 0.05). The best cut-off values for MTV and TLG were 20.3 cm³ and 72.3 g, yielding accuracy rates of 90.2% and 89.0% for predicting positive HER2 expression, respectively. Our further grouped study shows that in the gastric adenocarcinoma and Lauren classification groups, MTV was significantly negatively correlated with HER2 positivity. Notably, in mixed tumors, the AUC value reached as high as 0.85.ConclusionsThe negative correlations between MTV/TLG and HER2 status demonstrated that HER2-positive tumors are associated with reduced metabolic burden, providing imaging biomarkers for clinical prognostic assessment. Notably, subgroup analysis in gastric adenocarcinoma and Lauren classification subgroups revealed significant negative associations between MTV and HER2 positivity, highlighting MTV’s potential utility in predicting HER2 expression across histological subtypes of gastric cancer and supporting its role in precision oncology.